A five-year follow up study of stage I-IV of rectal cancer with an emphasis on epidermal growth factor over-expression - Kozłowska-Geller, Monika A.; Lewitowicz, Piotr; Głuszek, Stanisław Z. (Polish Journal of Pathology, 2021)
The key pro-proliferative pathway, based on EGFR-KRAS/BRAF-myc, is seen as the main goal of personalized therapy in rectal cancer. The objective of the study is to assess the EGFR immunoreactivity in rectal cancer and to estimate its relationship with the clinical outcome, especially as a predictor of poor outcomes. Patients: applying exclusion criteria, 102 patients with stage I-IV rectal cancer, who had undergone scheduled surgery during the period 2005-2011, were included in the study. There was a follow-up study with a span of 5 years from the date of the surgery. Immunohistochemistry using EGFR (EGFR Ab10, Clone111.6) was performed to detect an overexpression of the targeted receptor. Digital analysis of positive reactions of membranes was performed utilizing VisiopharmTM. The degree of EGFR intensity (log OR 0.854, OR 2.35, 95% Cl: 1.14–4.85, p = 0.021) is a significant factor in the prognosis of death within 2 years of surgery. The OS curve showed a significant decrease after 40 months from the date of surgery in the cases where EGFR had a high expression. The ROC curve for the cancer stage, according to the UICC classification and EGFR expression, in order to predict a 2-year RFS, reached a high specificity value (ROC = 0.81, p = 0.0408). Immunohistochemical EGFR expression is inexpensive, specific and broadly available.